Determinants of health-seeking behaviors among middle-aged women in Vietnam's rural-urban transition setting - Thao Thi Phuong Nguyen; Thao Thi Phuong Nguyen; Cuong Tat Nguyen; Cuong Tat Nguyen; Hieu Trung Do; Ha Thai Tran; Thuc Minh Thi Vu; Son Nghiem; Giang Thu Vu; Carl A. Latkin; Cyrus S. H. Ho; Cyrus S. H. Ho; et al. (Frontiers Media S.A., 2023)
IntroductionThe purpose of this study is to identify the health status and healthcare utilization factors associated with middle-aged women in the rapid urbanization context of Vietnam.MethodsA cross-sectional study with a systematic random sampling technique was conducted in Hung Yen city. A systematic random sampling technique was used to select a sample size of 362 middle-aged women. The collected data included socioeconomic characteristics, health issues, health service utilization, and social support for women in both urban and rural areas. Multivariate regression models were used to determine factors associated with health service utilization and the number of inpatient/outpatient visits.ResultsAmong 362 participants, the main chronic diseases were diabetes (12.8%), cardiovascular diseases (11.3%), and migraines (9.5%). The proportion of using inpatient and outpatient services among middle-aged women was relatively high (35.8 and 61%, respectively). Women having more support from family and friends were less likely to seek healthcare. Living in rural areas significantly increased the number of inpatient treatments. Regarding health service utilization, the percentage of people using outpatient treatment services accounted for 61.0%, while using inpatient treatment services was reported as 35.8%. The average number of outpatient and inpatient visits per participant were 1.3 and 0.9, respectively.ConclusionThis study revealed a relatively high rate of using healthcare services among women at midlife in a rapidly industrializing city in Vietnam. Screening programs should be implemented for early detection and treatment of chronic diseases in middle-aged women, especially for diabetes. Communication strategies should be adapted to raise awareness of rural women about regular health checkups, and counseling services of healthcare providers should be strongly reinforced. Lifestyle interventions and health promotion programs involving social support should be implemented to improve wellbeing and healthcare-seeking behaviors among middle-aged women.